The Relationship between the Classic Triad of Meningitis and Types of Meningitis - Budi Iftiyastuti, Selma Nissa; Rizkita, Leonny Dwi; Ihsana, Nuni; Selohandono, Andrianto (Newinera Publisher, 2024)
Meningitis is an inflammatory disease of the meninges caused by infection and non-infection. Based on WHO data for 2023, the CFR (Case Fatality Rate) for meningitis is 5.88%. In 2016 at the Southeast Asian level, Indonesia became the country with the highest mortality rate caused by meningitis. The classic triad of meningitis can assist in the early diagnosis of meningitis so that early management can be carried out to reduce mortality and morbidity if a cerebrospinal fluid examination is not possible immediately. Therefore, a study was conducted to determine the characteristics of meningitis patients, prevalence, and the relationship between the classic triad of meningitis and the incidence of infectious and non-infectious meningitis at Dr. Sardjito General Hospital Yogyakarta in 2017-2021. This study uses a cross-sectional method. The data taken is secondary data from 118 medical records of patients who have been treated. From the results, it was obtained that the highest characteristics and distribution were the age category 0-5 years (27.1%), male sex (51.7%), the most domicile outside DIY (54.2%), no/not yet school (36.4%) not/not yet working (38.1%), bacterial meningitis (39.0%), fever (89.8%), neck stiffness (78.8%). There is a significant relationship between the classic triad of meningitis and the type of meningitis (p-value 0.000). Among the three triads, it turned out that there was a solid relationship between the classic triad of meningitis and the type of infectious meningitis as indicated p-value by neck stiffness 0.000, fever 0.000, and headache 0.000.